Alzheimer''s disease and genetics of inflammation: a pharmacogenomic vision. (December 2007) - Vasto, Sonya; Candore, Giuseppina; Duro, Giovanni; Lio, Domenico; Grimaldi, Maria Paola; Caruso, Calogero
Inflammation plays a key role in Alzheimer disease, and dissecting the genetics of inflammation may provide an answer to the possible treatment. The next-generation therapy is based on a pharmacogenomics that will reconure new approaches to a drug used on definite people with specific dosage. The translation of pharmacogenomics into clinical practice will allow bold steps to be taken toward personalized medicine. In response to tissue injury elicited by trauma or infection, the inflammatory response sets in as a complex network of molecular and cellular interactions, directed to facilitate a return to physiological homeostasis and tissue repair. The role of an individual''s genetic background and predisposition for the extent of an inflammatory response is determined by variability of genes encoding endogenous mediators that constitute the pathways of inflammation. Due to its clinical relevance, in this review, the view on genetics of inflammation will be illustrated through a description of the genetic basis of a specific inflammatory disease, Alzheimer''s disease (AD). Several studies report a significantly different distribution, in patients and controls, of proinflammatory genes, alleles of which are under-represented in control subjects and over-represented in patients affected by AD. These studies will permit the detection of a risk profile that will potentially allow both the early identification of individuals susceptible to disease and the possible design or utilization of drug at the right dose for a desired effect –– a pharmacogenomic approach for this disease.